Measurement of buried undercut structures in microfluidic devices by laser fluorescent confocal microscopy - Li, Shiguang (2012)
Measuring buried, undercut microstructures is a challenging task in metrology. These structures are usually characterized by measuring their cross sections after physically cutting the samples. This method is destructive and the obtained information is incomplete. The distortion due to cutting also affects the measurement accuracy. In this paper, we first apply the laser fluorescent confocal microscopy and intensity differentiation algorithm to obtain the complete three-dimensional profile of the buried, undercut structures in microfluidic devices, which are made by the soft lithography technique and bonded by the oxygen plasma method. The impact of material wettability and the refractive index (n) mismatch among the liquid, samples, cover layer, and objective on the measurement accuracy are experimentally investigated.